Gagasan Integrasi Nilai-Nilai Adat Basandi Syarak Syarak Basandi Kitabullah (ABS SBK) Kedalam Pelajaran Pendidikan Agama Islam Pada Kurikulum Sekolah Dasar - Albert Albert; Iswantir Iswantir; Fauzan Ismail; Zainir Zainir (Publikasi Indonesia, 2022)
the curriculum in a broad sense needs to be continuously criticized. In this case, a formulation of PBM activities is needed that does not separate the science, skills and cultural values of the local community. This paper explains the idea of a formulation of the integration of Minangkabau cultural values which is contained in the adagium